Holey graphene anchoring of the monodispersed nano-sulfur with covalently-grafted polyaniline for lithium sulfur batteries. (March 2022) - Li, Jiajin; Li, Xinyu; Fan, Xin; Tang, Tao; Li, Ming; Zeng, Yaping; Wang, Heng; Wen, Jianfen; Xiao, Jianrong
Abstract: The homogeneous distribution of nano-sulfur onto 3D structures for the development of high-performance Li-S batteries (LSBs) is a top concern to solve the low utilization of sulfur, sluggish redox kinetics, and lithium polysulfide (LiPS) shuttle effect. Herein, a novel "egg tray" hierarchical architecture of confining and uniformly distributing nano-sulfur into a 3D holey graphene (HG) framework with polyaniline crosslinking (3DHG/NS/CPANI) via photo-assisted method was designed for high-mass-loading LSB cathode. Notably, HG contains both conductive skeletons as electron transfer paths and abundant void spaces in favor of homogenous sulfur anchoring. This configuration improves the contact between nano-sulfur and graphene for effective charge transportation and provides buffering space for volume variations during electrochemical processes. Moreover, a facile photo-assisted method was developed to cross link HG with polyaniline to act as an efficient polysulfide adsorbent, allowing nano-sulfur (NS) to be firmly embedded into the holes of graphene through physical and chemical effects, thus prohibiting the dissolution and shuttle effect of polysulfide. Considering these advantages, the prepared 3DHG/NS/CPANI electrode exhibited excellent performance with high sulfur utilization and specific capacity, resulting in specific discharge capacities at 0.5 and 1C of 1082 and 921 mA h −1, respectively, and small capacity decay of 0.04% per cycle over 500 cycles at 1C. The strategy in this work, which synergistically combines morphology control, nano-sulfur positioning, and structural engineering to enhance the electrochemical performance for Li−S batteries, will offer a valuable reference to energy storage and conversion advances. Graphical abstract: A novel "egg tray" hierarchical architecture of confining and uniformly distributing nano-sulfur into a 3D holey graphene (HG) framework with polyaniline crosslinking (3DHG/NS/CPANI) via photo-assisted method was designed. HG contains both conductive skeletons as electron transfer paths and abundant void spaces in favor of homogenous sulfur anchoring. This configuration improves the contact between nano-sulfur and graphene for effective charge transportation and provides buffering space for volume variations during electrochemical processes. Moreover, interchain cross-linking of polyaniline and covalent bonding of polyaniline to graphene oxide were realized by a photo-assisted cross-linking strategy to improve the chemical immobilization for polysulfides. Considering these advantages, the prepared 3DHG/NS/CPANI electrode exhibited excellent performance with high sulfur utilization and specific capacity. Image 1